A new species of Gomphidia Selys, 1854 (Insecta: Odonata: Anisoptera: Gomphidae) from the Western Ghats of India - Babu, R.; Subramanian, K.a. (Zootaxa, 2019)
A new species of Gomphidia Selys, 1854 is described from southern Western Ghats, India based on a male specimen. The new species is very distinct from all the known species of Gomphidia from Indian subcontinent. Revised keys to the males and known females of Gomphidia of India and Sri Lanka are provided.